Dynamic viability of the 2016 Mw 7.8 Kaikōura earthquake cascade on weak crustal faults - Thomas Ulrich (Nature Portfolio, 2019)
The 2016 Kaikōura earthquake in New Zealand raised the discussion about how a complex fault system operates. Here the authors propose a dynamic rupture scenario that reproduces key characteristics of the event and show that the fault system works at low apparent friction.